Exploration of nutrient content of traditional Tamil nadu recipe with solanumtrilobatum - S. VIJAYALAKSHMI; MARK KEITH FARADAY; A. WILFRED LAWRENCE; M. MURALI (International Journal of Pharma and Bio Sciences, 2016)
The majority of Indians are moving away from traditional to westernized food that offer a wide range of cuisines. Therapeutic based foods like herbs are fast disappearing with lack of systematic procedure. This research article is an attempt to resurrect South Indian therapeutic herbal recipes which we are fast being forgotten. Solanum trilobatum which is commonly known as Thuthuvalai is a medicinal plant which is extensively used in regional cooking in Tamil Nadu and the leaves of this plant was incorporated in the Adai recipe. Adai is a variety of the more popular traditional Tamil Nadu recipe. The main aim of the study is to standardize and prepare three Adai with different blends of lentils and herb Solanum trilobatum and to perform the sensory evaluation for its acceptance level and finally to calculate their nutritive content of all three herbal Adai using Nutritive value of Indian foods by NIN. The results of the sensory evaluation showed that the three Adai prepared with three different lentils was significantly different and it was proved for its high quality with its nutritive value. From this study it was concluded that this therapeutic Adai Code-C can serve as a different recipe as well as useful resource for the food industries particularly hotel industry who wish to restore the traditional therapeutic foods in their commercial market.